Character Education Values in the Ashaabul Uhduud Story: An Analysis of Al-Buruj Verses 4-8 - Ardiansyah, Ardiansyah; Suharto, Toto (Interdisciplinary Social Studies, 2022)
Background: This article discusses the values of character education in the stories contained in Al-Qur'an surah Al-Buruuj verses 4-8. This study was motivated by the moral crisis of students in Indonesia associated with the lack of character education that refers to religious values, so researchers took a story in the Qur'an, namely the Ashaabul Ukhduud story contained in Al-Buruuj verse 4-8 for taking the values of character education, it is hoped that it can be a solution to the moral crisis experienced in this country. Aim: This study is intended to answer problems, namely what are the values of character education in the Ashaabul Uhduud story? This problem is discussed and answered through the Holy Qur'an and its interpretations which are the guidelines and explanations of Muslim scriptures. Method: Writing this thesis uses library research or library research. The method used is the tahlili method. The source of writing data is taken from books or materials that are relevant to the discussion of problems in writing this essay. The source of this research data is distinguished writing into two groups, the first is primary data sources originating from the Qur'an and interpretations then the second source is secondary data sources originating from sources/books that are still related to research problems. Findings: The values contained in Al-Buruj verses 4-8 are honesty, empathy, nationalism, tolerance, religion, discipline, courage, being a learner throughout life, and responsibility.